PENGARUH MOTIVASI DAN KECERDASAN EMOSIONAL TERHADAP KEMANDIRIAN BELAJAR SISWA PADA PEMBELAJARAN DARING SEKOLAH BATAM (STUDI PADA SDN 005 SEKUPANG BATAM) - Andria Siska; Abdul Mujib; Dewi Artati Padmo Putri (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
This study aims to analyze the motivation and emotional intelligence of students' learning independence in Online Learning Schools in Batam. The research method uses a quantitative approach, correlational design. The population of this study were 339 students. Sampling technique using disproportionate stratified random sampling set a sample of 183 respondents. Data collection techniques through questionnaires, interviews, and documentation. The results showed that the variables of motivation and emotional intelligence had a significant and simultaneous effect on students' learning independence. The results of the t test show that the motivation variable has a significant effect on student learning independence, and emotional intelligence also has a significant effect on learning independence. The coefficient of determination is 0.315 or shows that 31.5% of students' learning independence is influenced simultaneously by the variables of motivation and emotional intelligence.